Magnetic properties, magnetoresistance, and magnetic-field-induced phase transitions in Tb0.95Bi0.05MnO3 and Eu0.8Ce0.2Mn2O5 multiferroics - Sanina, V. A.; Golovenchits, E. I.; Zalesskiĭ, V. G. (Physics of the solid state, 2008)
This paper reports on a study of the magnetic properties, magnetoresistance, and phase transitions in the semiconducting manganite multiferroics Tb 0.95 Bi 0.05 MnO 3 and Eu 0.8 Ce 0.2 Mn 2 O 5 whose dielectric properties have been a subject of an earlier study. An analysis of these properties has led us to the conclusion that the above crystals at temperatures T ≥ 180 K undergo phase separation with the formation of a dynamic periodic alternation of quasi-2D layers of manganese ions in different valence states, i.e., charge-induced ferroelectricity. This state exhibits a giant permittivity and ferromagnetism in the layers containing Mn 3+ and Mn 4+ ions. At low temperatures ( T < 100 K), the phase volume is occupied primarily by the dielectric phase. Studies of the magnetic properties and the effect of the magnetic field on the dielectric properties of crystals substantiate the scenario of the formation of a state with giant permittivity put forward by us. At low temperatures, Tb 0.95 Bi 0.05 MnO 3 exhibits features at the points of phase transitions in pure TbMnO 3 . A ferromagnetic moment is observed to exist at all the temperatures covered. At the boundaries of the quasi-2D layers, magnetic-field-induced jumps of the electrical resistivity caused by metamagnetic transitions in the layers with Mn 3+ and Mn 4+ ions are observed. At temperatures T ≥ 180 K, the electrical resistivity undergoes a periodic variation in a magnetic field which is a manifestation of carrier self-organization. A high magnetic field is capable of shifting the phase transition from 180 K to higher temperatures and inducing additional phase transitions.